Manajemen Perioperatif Trepanasi Dekompresi Subdural Hemorrhage (SDH) dengan Hemofilia A - Praniarda, Andika Satria; Laksono, Buyung Hartiyo (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2022)
Haemofilia A is congenital blood disease with female carrier, usualy found in male patient and happened for life. When one coagulation factor is lost or disfunction, coagulation mechanism will be disturbed and the bleeding difficult to stop. In this day, brain injury caused by trauma is the first cause of death in patient with haemophilia. Surgery in intracranial bleeding must be done as much as possible to get better prognosis. Blood evacuation must undergo quickly but very risky for rebleeding. Factor VIII must be given as soon as possible for treatment in severe haemophiliaA patient with acute bleeding. Maintenance anesthesia also include decrease risk of hypertension and tachicardia for minimalize the ongoing bleeding.Male 17thyears old diagnose with brain injury 2x4 caused by subdural hemorrhage (SDH) left frontotemporoparietal region and cerebral edema followed by subfalcine herniation to the right and haemophilia A planned for decompression evacuation of SDH. Patient got factor VIII 4000unit before operation. Intraoperative bledding are 1100cc and get 1940cc of blood product for stabilize the haemodynamic. Post operative was observe in Intensive Care Unit and went for extubation after 8thday after in good condition.Hemofilia adalah kelainan darah bawaan yang serius dengan wanita sebagai pembawa, terutama didapatkan pada pria dan berlangsung sepanjang hidup dimana hemofilia A merupakan tipe hemofilia tersering. Ketika salah satu faktor yang diperlukan untuk pembekuan darah hilang atau memiliki fungsi yang tidak memadai, mekanisme koagulasi yang terganggu menyebabkan perdarahan yang tidak dapat dihentikan. Saat ini, penyebab kematian paling umum di antara pasien hemofilia adalah perdarahan otak karena trauma kepala. Kasus perdarahan intrakranial sebisa mungkin dilakukan tindakan operasi segera untuk mendapatkan prognosis yang lebih baik. Tindakan evakuasi perdarahan harus dikerjakan dalam waktu singkat namun memiliki resiko tinggi terjadinya perdarahan ulang. Pemberian penggantian faktor VIII rekombinan untuk pengobatan perdarahan akut pada pasien hemofilia A berat harus dilakukan segera. Rumatan anestesi juga harus mencakup penurunan resiko hipertensi dan takikardia untuk meminimalkan terjadinya perdarahan. Laki-laki usia 17 tahun dengan diagnosa penurunan kesadaran cedera kepala 2x4 karena perdarahan intracranial subdural hemorrhage (SDH) regio frontotemporoparietal sinistra dan edema cerebri hari ke 4 disertai herniasi subfalcine ke kanan dengan hemofilia A direncanakan tindakan trepanasi dekompresi evakuasi SDH. Pasien mendapatkan injeksi faktor VIII 4000 unit sebelum operasi. Durante operasi perdarahan 1100cc dan mendapat transfusi 1940cc produk darah hingga hemodinamik stabil. Post operatif pasien dilakukan perawatan di ICU selama 8 hari, dilakukan extubasi setelah kondisi membaik.Perioperative Management Trepanation and Decompression Subdural Hemorrhage with Haemophilia AAbstractHaemofilia A is congenital blood disease with female carrier, usualy found in male patient and happened for life. When one coagulation factor is lost or disfunction, coagulation mechanism will be disturbed and the bleeding difficult to stop. In this day, brain injury caused by trauma is the first cause of death in patient with haemophilia. Surgery in intracranial bleeding must be done as much as possible to get better prognosis. Blood evacuation must undergo quickly but very risky for rebleeding. Factor VIII must be given as soon as possible for treatment in severe haemophilia A patient with acute bleeding. Maintenance anesthesia also include decrease risk of hypertension and tachicardia for minimalize the ongoing bleeding. Male 17th years old diagnose with brain injury 2x4 caused by subdural hemorrhage (SDH) left frontotemporoparietal region and cerebral edema followed by subfalcine herniation to the right and haemophilia A planned for decompression evacuation of SDH. Patient got factor VIII 4000unit before operation. Intraoperative bledding are 1100cc and get 1940cc of blood product for stabilize the haemodynamic. Post operative was observe in Intensive Care Unit and went for extubation after 8th day after in good condition.